From Personal to Communal: The Conflict among Sunni-Shi`ite in Sampang, East Java - Mukhsin Achmad; Khoiruddin Khoiruddin; Moch Nur Ichwan (Universitas Islam Negeri Sunan Kalijaga, 2019)
This paper discusses conflict of Sunni-Shi`a which occurs in East Java. The relationship among them is dominated by contravention, competition/contestation and conflict. The contravention occurs during the emergence of Shi`ite community in Madura. when the majority of Madurese community who are mostly Sunni rejected their first existence. For instance, Ali Karrar Shinhaji (The local Ulama) was against the decision of Kyai Makmun to deliver his son, Tajul Muluk, to study at YAPI Bangil that affiliated with Shi`i. The conflict further escalates because of Tajul Muluk’s and Roisul Hukama’s personal problem. Eventually, the conflict thus increases on the higher level in Sampang and in Province level. This paper examines how the conflict of Sunn-Shi`i emerges, whether it is a pure of family conflict or involves the conflict among the religious authorities in Sampang society. This paper utilizes Myers’ theory combined with critical discourse analysis on the causal factor of conflict. Through both bibliographical and empirical investigation, this paper finds that the conflict emerges from family to province, when the contestation and conflict between Tajul Muluk and Roisul Hukama increase to higher level, from community of Sampang to East Java Province. In addition, this conflict also involves the contestation among religious authorities, when the positivisation of fatwa, which is morally binding, transforms into a public policy of the government that legally binding is the evident of this conflict.